The The Efect Of Bokashi Pig Manure to The Growth of Eggplant (Solanum melongena) - Ziraluo, Yan Piter Basman (International Journal of Science, Technology & Management, 2020)
This study aims to determine the effect of pig poop bokashi on teh growth of eggplant (Solanum melongena). the experimental research method (True Experiment) with a Completely Randomized Design (CRD) consisting of six treatments and five replications. The population of this study was 30 eggplant (Solanum melongena). The research simple was selected using a simple random sampling strategy. The research sample was 30eggplant (Solanum melongena). The research data were analyzed using the Kolmogrov-Smirnov test for normality, Bartlett test for homogenity, and ANOVA for testing the hypothesis. The research findings obtained indicate that the influence of pig poop bokashi on the growth of eggplant (Solanum melongena)both in plant height, stem diameter, and number of leaf strands. So it can be concluded that pig poop bokashi can be used as an alternative to replace the presence of inorganic fertilizer (chemical fertilizer). Suggestions offered by researchers, should the use of bokashi pig poop manure can be further improved among farmers and the community in general because in addition to addressing the use of inorganic fertilizer that can affect the quatlity of soil and plants also affect finances that must be spent to buy inorganic fertlizer.